The Effect of Dietary Supplement Coriander Seed (Corindrum sativum L) on Fatty Acid Composition of Selected Tissues in Japanese Quail (c) - Ertas , Osman Nihat (International Journal of Poultry Science, 2013)
In This Experiment, Four hundred ninety, 3 day-old Japanese quails were randomly divided into five trial groups of 98 birds (49 males and 49 females) in each group according to diets, in the control group, the birds were fed with a basal diet (24% Crude proteins and 2900 Kcal metabolizable energy/kg. Four different levels of coriander seeds 0.5% (0.5 coriander group), 1% (1% coriander group), 2% (2% coriander group) and 4% (4% coriander group) were added to the basal diets. We were conducted to evaluated the effect of dietary supplemented coriander seed on fatty acid composition of selected tissues (Heart Tissues, Thigh Muscle and thigh Skin) in quails. Fatty acid profiles for selected tissues were altered by added coriander seeds in diets. While all tissues total PUFA concentration (especially n-3 PUFA) was higher 4%, 2% coriander seed according to 0.5%, 1% and control groups (P0.05) and increased PUFA (P